EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN JIGSAW BERBANTU MEDIA FLASH PADAMATERI DIMENSI TIGA DITINJAU DARI GAYA BELAJAR SISWA KELAS XI SMK DI KABUPATEN SRAGEN TAHUN AJARAN 2015/2016 - Kurniawati, Rina; Riyadi, Riyadi; Sujadi, Imam (Journal of Mathematics and Mathematics Education, 2017)
Abstract: This research was purposed to determine: (1) which one produced better mathematics learning achievement, cooperative learning model type Jigsawand Jigsaw Flash, or direct instruction; (2) which one had better mathematics learning achievement between students with visual learning style, those with auditory or those with kinesthetic learning style; (3) on each learning style, which one learning model that produced better mathematics learning achievement, cooperative learning model type Jigsawand Jigsaw Flash or direct instruction (4) on each learning model, which one student had better mathematics learning achievement , student who had visual learning style, those with auditory or those with kinesthetic learning style. This study was a quasi-experimental study with factorial 3x3 design. Population in this research were eleventh grade students of Vocational High School in Sragen. Sample collection were done by stratified cluster random sampling. Data collection were done by the method of documentation in order to test the balance of the population, the questionnaire were used to determine the students learning style and test were used to know the students achievement on material dimension three. Data analysis techniques used ANAVA two ways with unbalanced cells. The results of this study concluded as follows (1) cooperative learning model type Jigsaw Flash gave better mathematics learning achievement than cooperative learning type Jigsaw and direct instruction, cooperative learning type Jigsaw gave better mathematics learning achievement than direct instruction; (2) Students with kinesthetic learning style had better mathematics learning achievement than students with visual learning style and auditory learning style; students with visual learning style had better mathematics learning achievement than students with auditory learning style; (3) on each learning style, cooperative learning model type Jigsaw Flash gave better mathematics learning achievement than cooperative learning type Jigsaw and direct instruction, cooperative learning type Jigsaw gave better mathematics learning achievement than direct instruction; (4) on each learning model (Jigsaw, Jigsaw Flash, and direct instruction), students with kinesthetic learning style had better mathematics learning achievement than students with visual learning style and auditory learning style with visual learning style had better mathematics learning achievement than students with auditory learning style.Keywords: Learning Model, Jigsaw, Jigsaw Flash, Learning Style, learning achievement